Factors in adherence to physiotherapy treatment in a national rehabilitation institute - Moya Nolli, Carmen Rosana (2022)
Objective: To determine the factors in adherence to physiotherapy treatment in a Peruvian rehabilitation institute. Material and methods: The cross-sectional descriptive-correlational study was carried out on a sample of 110 patients treated at the Department of the Motor Unit and Pain of the National Institute of Rehabilitation. A probabilistic sampling and a survey were applied, with an instrument made up of 20 questions to determine intrinsic and extrinsic factors to treatment adherence, whose reliability was 0.814, according to Cronbach's alpha. Results: 49.1 % are female and are adherent to physiotherapy treatment. Likewise, the intrinsic and extrinsic factors are related to physiotherapy adherence in treated patients. Conclusion: Adherence to treatment does not have to do only with the physiotherapist, but also with any other professional; understanding the real, sincere and honest commitment of the patient, and considering the advice of the physiotherapist.